Effect of diet on live weight and egg weight of backyard hens during the rainy season - Barocio-Urue, JN; Juárez-Caratachea, A; Gutiérrez-Vázquez, E; Pérez- Sánchez, RE; Ortiz-Rodríguez, R (Austral Journal of Veterinary Sciences, 2017)
ABSTRACT. The objective was to determine the effect of diet on live weight (LW) and egg weight (EW) of backyard hens (BH) during the rainy season in the Bajío region of the state of Michoacán, Mexico. Seventeen municipalities were sampled, where 101 BH (six hens/municipality) were captured and weighed and 101 eggs (six eggs/municipality) were harvested and weighed. The crops of the captured hens were removed Post-sacrifice, the organic content/crop (OCC) was classified and weighed by components, to later perform chemical compositional analysis. Data were analysed using generalised linear models and the differences between municipalities were obtained by the method of least squares means. The weight of the OCC (36.4 ± 22.4 g) was affected by the municipality (P<0.001), but not by the LW of the BH (P>0.05). Commercial feed (8.1 ± 6.0 g), grains: maize and sorghum (13.9 ± 13.5 g) kitchen waste (1.5 ± 2.9 g), herbaceous (0.6 ± 0.9 g) and insects (0.3 ± 0.7 g) were found in the crop. According to the commercial feed (COF) component, two feeding systems (FS) were identified: traditional FS, without COF and nontraditional FS, with COF. The diets of both FS were similar (P>0.05) in nutritional composition and do not meet the nutritional requirements of the hens. The LW (1.567 ± 0.316 kg) and EW (51.3 ± 1.0 g) of the BH cannot be completely attributed to the diet consumed during the rainy season.